Chapter 8 Vulnerability through the Invulnerable Transhuman Lens Ethics and Disruption of Emotional Connections and Mental Affections in Maniac (2018) - Chapman, Ana (Taylor & Francis, 2024)
This chapter examines representations of mental conditions in the dystopian backdrop for transhumanism in Netflix's series Maniac. In the quest for human perfectionism, vulnerabilities are exposed and intensified by technological disruption. The transhumanist promise of human enhancement is presented in the series as hindering basic affect, self-awareness, and emotional response that in turn makes for human relational interdependence. Accordingly, it focuses on how the invulnerable transhuman figure is posed as a threat to subjectivity and autonomy. Vulnerability studies, ethics of care, neuroscientific theories on emotional sensations (interoception and exteroception awareness), and posthumanism give support to the chapter's main thesis that this series posits characters' fundamentally relational essence for wellbeing as based on rather different ethical grounds from those seen in the transhumanist paradigm, which is based on individualism, independence, autonomy and/or self-sufficiency via technology. For this study, theories on transhumanism, vulnerability, emotional, and ethical studies are introduced to give way to the analysis of the series. Firstly, the chapter explores Maniac's representation of technology and mental health in a setting where characters seem to be in search of connections to move on to a discussion of the implications of relational and emotional engagement for characters' wellbeing and autonomy.